Avaliação do processo de ensino interdisciplinar na educação ambiental utilizando visitas guiadas em áreas verdes - Zoccoli, Chrislaine Vitcoski (2016)
In the process of teaching science, conduct field activities in protected areas, ie, non-formal environments, enables stimulate and enrich different methodological paths that lead to learning critically reflective and responsible front to environmental issues. These practices observation activities let you explore diverse content, sensitize students to the preservation and conservation, through direct contact with the environment, and improve the understanding of the phenomena learned in class theoretically. However, that field activities are effective, it is essential to be well prepared and properly exploited. Therefore, the present study has the objective of proposing activities using protected areas in interdisciplinary teaching process and environmental education, focused on the theme generator Environment, which was applied in two public schools in the city of Curitiba, Paraná.Primeiramente sought to identify, through questionnaires and interviews, which were the methods that teachers have applied to work on environmental issues, analyzed the educational use of protected areas as part of the lessons, and how to envision an interdisciplinary learning with this theme. Survey was carried out in official government documents to the basic contents of the different areas of knowledge of elementary school I and II, related to the theme environment. This diagnosis was to identify the relationship between the cross-cutting issues, and their joint operation in an interdisciplinary way relating to the theme. then proceeded to a quantitative and qualitative analysis of the ten teachers participating in this study, who were observed and interviewed before the field activity, and after the implementation of the same in a unit Conservação.Como result was noted a positive predominance of speeches and responses to the possibility of insertion of Federal Law No. 9.795 / 99 environmental Education in the teaching practice of teachers of various disciplines of basic curriculum, the importance of expansion of methodological and pedagogical strategies for meaningful learning about the environment, even with so many difficulties encountered by teachers to access the protected areas. Regarding analyzed and raised in official documents contents, it was found that the curriculum components of Art, Science, Physical Education, Geography, History, English Language and Mathematics, presented various contents that could be articulated and explored using the theme Half EA Environment in field activities. It was prepared the Field Activity Guide to operate in protected areas in science education with proposed interdisciplinary application, as the final product of this research.